Dioscorea alata enhances on the corpus luteum histology in an endometriosis mouse model - Makiyah, Sri Nabawiyati Nurul; Rahmawati, Suci Nur (Science Midwifery, 2026)
Endometriosis is a chronic inflammatory disease that causes ovarian damage and infertility. Dioscorea alata contains anti-inflammatory and antioxidant agents. This study examined the effect of ethanol extract of Dioscorea alata (EEDA) on the histology of corpus luteum in an endometriosis mouse model. This research is a quasi-experimental with a post-test-only controlled group design. Twenty-four mice were divided into six groups: control (C), negative control (NC) induced endometriosis model, positive control (PC) induced endometriosis model and letrozole, and three treatment groups induced endometriosis model and EEDA 50, 250, and 500 mg/kg body weight (T1, T2, T3). The number and diameter of corpus luteum analyzed with Kruskal-Wallis test, One-way ANOVA, and Duncan's test. The number of corpus luteum decreased in negative control group and increased significantly in the treatment groups (P = 0.038). The diameter of corpus luteum decreased in the negative control group and increased non-significantly in the treatment groups (P = 0.206). The conclusions of this research prove that EEDA has a positive effect both the number and diameter of corpus luteum in an endometriosis mouse model.